ANALISIS PENGARUH MARKETING PUBLIC RELATIONS DAN CITRA KAMPUS TERHADAP MINAT MENJADI MAHASISWA STIEPARI - Asih Niati; Heri Prabowo (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2015)
This research analyzes many factors which can influence someone to be come STIEPARI Students. The problem of the research refers to the phenomena of STIEPARI wihich does not fulfill new students expectation target. The purpose of the research is to enhance the interest target to be students of STIEPARI Semarang.The data analysis technique to the rest the hypotesis is the Structural Equation Model (SEM) which is operated with the Analysis of Moment Structure (AMOS) Versi 18.0. The result shows that marketing public relation anda campus image veriable as an intervening variable in this research is correct. It means that marketing public relation influences the campus image which correlates the decision to be STIEPARI students.Kata Kunci : marketing public relation, campusimage & becoming STIEPARI students